2022
DOI: 10.1155/2022/7357566
|View full text |Cite
|
Sign up to set email alerts
|

HPV-Related Prognostic Signature Predicts Survival in Head and Neck Squamous Cell Carcinoma

Abstract: Background. Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers, worldwide. Considering the role of human papilloma virus (HPV) in tumor development and sensitivity to treatment of HNSCC, we aimed to explore the prognostic classification ability of HPV-related signatures in head and neck cancer. Methods. HPV-related signatures were screened out based on Gene Expression Omnibus (GEO) and the Cancer Genome Atlas (TCGA) databases. HPV-related signatures with prognostic value were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Here, we established a new anoikis-related prognostic signature by identifying 18 ARGs with prognostic significance. Compared with 5 other signatures, [21–25] our model showed better predictive efficacy in predicting the prognosis of HNSCC patients. Moreover, we found that our model had potential ability to predict the sensitivity to chemotherapy and immunotherapy, which may suggest immunotherapeutic and chemotherapeutic strategies for patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we established a new anoikis-related prognostic signature by identifying 18 ARGs with prognostic significance. Compared with 5 other signatures, [21–25] our model showed better predictive efficacy in predicting the prognosis of HNSCC patients. Moreover, we found that our model had potential ability to predict the sensitivity to chemotherapy and immunotherapy, which may suggest immunotherapeutic and chemotherapeutic strategies for patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Researchers have identified some prognostic signatures for HNSCC in recent years. [21][22][23][24][25]37] However, to our knowledge, few have investigated the relationship between anoikis and HNSCC. Here, we established a new anoikis-related prognostic signature by identifying 18 ARGs with prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factor DMRTA2 is involved in gonadal differentiation and CNS development taking part in determining cell fate decisions. The potential role of DMRTA2 as a prognostic marker was indicated in several non-CNS cancers as this gene appeared deregulated in gene expression [ 43 , 44 ] or DNA methylation-based signatures [ 45 , 46 ]. Tumor cell origin studies indicated glioblastoma originates from neural stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%